Within-Country Poverty Convergence: Evidence from Mexico - Luis-Felipe López-Calva; Eduardo Ortiz-Juarez; Carlos Rodriguez Castelan (Institute of Labor Economics (IZA), 2020)
Trends in aggregate growth and poverty reduction hide a multiplicity of development processes at the local level. The analysis reported in this paper exploits a unique panel dataset of poverty maps covering almost 2,400 municipalities in Mexico and spanning 22 years, first, to test hypothesis that there is within-country income convergence. Second, through a decomposition of the poverty convergence elasticity, the analysis investigates whether this convergence, if it exists, has translated into poverty convergence. In a context of overall stagnant economic growth and poverty reduction since 1990, the analysis finds evidence of both income and poverty convergence among municipalities. As a cause of these, the results point to a combination of positive performance among the poorest municipalities and stagnant or deteriorating performance among more well off municipalities. Redistributive programs such as cash transfers to poor households have played an important role in driving these results by bolstering income growth among the poorest municipalities, while also inducing progressive changes in the distribution of income.
Keywords: I32; O47; O54; R11; 330; income; inequality; convergence; poverty convergence elasticity; small area estimation